Patterns and predictors of e‐cigarette, cigarette and dual use uptake in UK adolescents: evidence from a 24‐month prospective study. (25th July 2019) - Conner, Mark; Grogan, Sarah; Simms‐Ellis, Ruth; Scholtens, Keira; Sykes‐Muskett, Bianca; Cowap, Lisa; Lawton, Rebecca; Armitage, Christopher J.; Meads, David; Schmitt, Laetitia; Torgerson, Carole; West, Robert; et al.
Abstract: Background and Aims: To assess prevalence and predictors of e‐cigarettes/cigarettes patterns of use in adolescents in England. Design: Prospective study with 24‐month follow‐up of e‐cigarette/cigarette ever/regular use with data from an intervention evaluation. Setting: Forty‐five schools in England (Staffordshire and Yorkshire). Participants: A total of 3210 adolescents who, at baseline, were aged 13–14 years and had never used e‐cigarettes/cigarettes. Measurements: Based on e‐cigarette/cigarette ever use at follow‐up, six groups were created: (a) never user, (b) e‐cigarette only, (c) cigarette only, (d) dual use—order of use unclear, (e) dual use—e‐cigarettes used first and (f) dual use—cigarettes used first. Baseline measures were: gender, ethnicity, socio‐economic status, impulsivity, family plus friend smoking and smoking‐related beliefs (attitude and perceived behavioural control). Findings: In groups (a) to (f), there were 71.5, 13.3, 3.3, 5.7, 2.9 and 3.4% adolescents, respectively. Among groups using cigarettes, regular smoking was more prevalent in group (f) (dual use—cigarettes used first) [17.6%, 95% confidence interval (CI) = 10.4, 24.8] than in groups (c), (d) and (e) combined (7.3%, 95% CI = 4.7, 9.9). Among groups using e‐cigarettes, regular use was less prevalent in group (b) (e‐cigarette only) (1.9%, 95% CI = 0.6, 3.2) than in groups (d), (e) and (f) combined (12.2%, 95% CI = 8.9, 15.5). Higher impulsivity plus friends and family smoking were predictive of being in groups (b) to (f) compared with group (a) (never users). Males were more likely to be in group (b) compared to group (a); females were more likely to be in groups (c) to (f) compared to group (a). Conclusions: Regular use of e‐cigarettes/cigarettes varies across groups defined by ever use of e‐cigarettes/cigarettes. Interventions targeted at tackling impulsivity or adolescents whose friends and family members smoke may represent fruitful avenues for future research.